Barriers of green building implementation during pre-contract stage / Rabbiatul Rejina Mohd Ridah and Husrul Nizam Husin - Mohd Ridah, Rabbiatul Rejina; Husin, Husrul Nizam (2019)
Green building is already existing longer in construction industry and many countries had succeeded to implement the technology. But in Malaysia, many barriers have identified due to green building adoption especially among the consultant team. Quantity surveyors are to perform financial control, cost and contractual administration of a project from inception to completion. But they also agreed that, the evolution of the quantity surveying profession due to changes from traditional to green construction become challenges and global threats. The aim of this study is to establish the best practice of green building implementation in Malaysia from quantity surveyors' profession. The objective is to identify the barriers of green building implementation during pre-contract stage. The method used was questionnaire survey and the responses were from 56 quantity surveyors who involved in green building projects in Malaysia. The data collected analyzed by SPPS version 25. This study identified that the highest mean value for barriers of green building implementation during pre-contract stage is during tendering stage longer time during the selection process and lack of experience in green projects.